Fracture-Dedicated Prosthesis Promotes the Healing Rate of Greater Tuberosity in Reverse Shoulder Arthroplasty: A Meta-Analysis - He, Shu-Kun; Liao, Jing-Ping; Guo, Jin-Hai; Huang, Fu-guo (Frontiers in Surgery, 2021)
Introduction: Reverse shoulder arthroplasty (RSA) is becoming popular in the treatment of complex proximal humeral fractures (PHF). Greater tuberosity healing may influence functional outcomes and range of motion (ROM) of shoulder after RSA. In addition, the design of prosthesis may impact the healing rate of greater tuberosity. The purpose of our study is to know 1) does the healing of greater tuberosity affect the functional outcomes and ROM of shoulder; 2) does the design of prosthesis affect the healing rate of greater tuberosity. Materials and Methods: PubMed, Ovid/Embase and the Cochrane Library were searched for studies comparing the clinical outcomes between healed groups and non-healed groups after RSA. Results: For functional outcomes, the result showed that the healed group had better Constant scores (CS) (P<0.0001). For ROM, the healed group showed better flexion (P<0.0001), abduction (P=0.02), external rotation (P<0.00001) of shoulder. For the design of prosthesis, the mean healing rate of greater tuberosity (82.7%) in patients with fracture-dedicated prosthesis was higher than those (63.0%) in patients with standard prosthesis. Subgroup analyses showed that the CS (P=0.12) and abduction (P=0.96) of patients using fracture-dedicated prostheses were not different between healed groups and non-healed groups. Meta-regression showed that there was no significant relationship between the design of prosthesis and CS (P=0.312), flexion (P=0.422), or external rotation (P=0.776). Conclusions: Our meta-analysis showed that healed groups could obtain better functional outcomes and ROM than non-healed groups. In addition, fracture-dedicated prostheses promoted the healing rate of greater tuberosity.